Interior view of the remains of the ancient Church of St. Michael, Aldgate - Wise, William; Shepherd, Thomas Hosmer (Tufts Archival Research Center, 2008)
With a plan of the groining of the roof, and of the site of the building. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 2.